Kracauer and Tarkovsky’s Cinema of Redemptive Estrangement - Daniel Sullivan (Film-Philosophy)
Despite striking parallels between their philosophies and artistic work, there have been no prior dedicated studies of the reinforcing ideas of Siegfried Kracauer and Andrei Tarkovsky. I contend with other interpreters that Kracauer’s philosophy of film is best understood as a form of revelationism, with strong sociological and ontological theses about the nature of modern psychological life and the medium specificity of film. Essentially, Kracauer felt that certain films which adhere to what he called “truly cinematic” content by depicting the naturalistic “flow of life” have the potential to awaken in viewers a psychological reconnection to the concrete material world, in contrast to the experience of abstraction characteristic of modernity. Having presented Kracauer’s philosophy, I outline strong convergences in the philosophy and aesthetics of Tarkovsky, and illustrate these parallels through close analysis of Tarkovsky’s 1979 film Stalker. In the third section of this article, I further explore the converging revelationist philosophies of Kracauer–Tarkovsky by confronting them with critiques which were levied by Theodor Adorno (against Kracauer) and Fredric Jameson (against Tarkovsky). The reconstructed debate between these four critic/practitioners touches on central issues for film criticism, including methodological approaches of ontology versus dialectics and the question of how to represent utopic impulses in cinema.